Analysis of integrity programs of companies listed on the Ibovespa from the perspective of the criteria indicated in the CVM reference forms - Colares, Ana Carolina Vasconcelos (2024)
The search for integrity in companies has become even more crucial in a globalized and highly regulated business scenario. Integrity programs emerge as essential tools to prevent corruption and misconduct in companies. However, the implementation and enforcement of these policies face challenges, such as organizational culture, resource allocation and monitoring. This article analyzes the structure and effectiveness of the integrity programs of 79 companies listed on B3's Ibovespa. This choice is based on the fact that they play a fundamental role in the Brazilian economy, influencing the financial market and contributing to the country's economic development. Conducted using the multiple case study method and using data published by companies, the research revealed an impressive average of 86% adherence to the standards established by the CVM. Although all companies have codes of ethics, it is noteworthy that 78% were not clear in their risk assessment. Despite the areas identified for improvement, significant progress and a robust integration of compliance programs in organizations were observed. The study emphasizes the notable convergence between the programs analyzed, highlighting the relevance of regulatory entities, such as CVM and B3, in consolidation of the Brazilian capital market. Among the entities examined, 68% achieved the highest level of governance, demonstrating an active search for excellence. As a recommendation for future research, an integrated analysis of integrity programs with other sources is suggested, providing a more comprehensive and in-depth assessment.